Warmth and competence perceptions of key protagonists are associated with containment measures during the COVID-19 pandemic: Evidence from 35 countries - Friehs, Maria-Therese; Kotzur, Patrick F.; Kraus, Christine; Schemmerling, Moritz; Herzig, Jessica A.; Stanciu, Adrian; Yzerbyt, Vincent (Nature Portfolio, 2022)
It is crucial to understand why people comply with measures to contain viruses and their effects during pandemics. We provide evidence from 35 countries (N-total = 12,553) from 6 continents during the COVID-19 pandemic (between 2021 and 2022) obtained via cross-sectional surveys that the social perception of key protagonists on two basic dimensions-warmth and competence-plays a crucial role in shaping pandemic-related behaviors. Firstly, when asked in an open question format, heads of state, physicians, and protest movements were universally identified as key protagonists across countries. Secondly, multiple-group confirmatory factor analyses revealed that warmth and competence perceptions of these and other protagonists differed significantly within and between countries. Thirdly, internal meta-analyses showed that warmth and competence perceptions of heads of state, physicians, and protest movements were associated with support and opposition intentions, containment and prevention behaviors, as well as vaccination uptake. Our results have important implications for designing effective interventions to motivate desirable health outcomes and coping with future health crises and other global challenges.
Keywords: Stereotype Content; Model; Behaviors